The pendulum adaptive frequency oscillator. (1st November 2022) - Li, XiaoFu; Kallepalli, Pawan; Mollik, Tushar; Shougat, Md Raf E Ul; Kennedy, Scott; Frabitore, Sean; Perkins, Edmon
Abstract: Adaptive oscillators are a type of nonlinear oscillator that are capable of learning and storing information in plastic states. Here, a typical mechanical pendulum is modified to have an adjustable rod length to create a pendulum adaptive frequency oscillator. Since the resonance frequency of the pendulum is a function of the rod length, this allows the pendulum to learn and encode frequency information from an external source. An experimental pendulum adaptive frequency oscillator is designed and constructed, and its performance is compared to numerical simulations. This nonlinear pendulum was approximated as a Duffing oscillator through the method of multiple scales to determine the physical constants of the experiment by using a curve fit. Utilizing the pendulum adaptive frequency oscillator's dynamics, this system is able to learn a resonance condition and store this information in the rod length. This causes the system to seek resonance, even with considerable nonlinearity. As pendulums can be used to harvest energy, this type of adaptation could be used to further exploit vibratory energy sources. Highlights: The pendulum is modified to be an adaptive frequency oscillator. Pendulum adaptive frequency oscillator learns resonance by modifying rod length. This system maintains a large amplitude over a wide range of frequencies. The method of multiple scales is used to obtain parameters of the experiment. Experimental prototype behaves qualitatively similar to the numerical simulations.